An adhesive SERS substrate based on a stretched silver nanowire-tape for the in situ multicomponent analysis of pesticide residues. Issue 10 (27th February 2023) - Dai, Xing; Xue, Danni; Liu, Xiaohan; Gu, Chenjie; Jiang, Tao
Abstract : Two essential factors in powerful surface-enhanced Raman spectroscopy analysis of trace pesticide residues are viz., high sensitivity and efficient sampling. Abstract : Two essential factors in powerful surface-enhanced Raman spectroscopy analysis of trace pesticide residues are viz., high sensitivity and efficient sampling. Herein, owing to elastic properties, a stretched Ag nanowire (Ag NW)-tape under the strain of 15% formed a wrinkled structure with periodic microridges and microgrooves, where abundant nanogaps were generated by the aggregated Ag NWs. Compared with the unstretched Ag NW-tape substrate, an appreciable signal enhancement of the modified 4-mercaptobenzoic acid (4-MBA) molecules with a ratio of 2.6 was discerned from the sophisticated SERS substrate due to the electromagnetic enhancement induced by the relatively high density of "hot spots" around the Ag NW aggregates. The as-fabricated Ag NW-tape substrate performed admirably in detecting 4-MBA and demonstrated an enhancement factor of 1.16 × 10 6 . Moreover, for the in situ detection of tetramethylthiuram disulfide, thiabendazole, and their mixture, the relatively high recovery rates of over 88% were favorably realized by the Ag NW-tape substrate with superior sensitivity, distinct flexibility, and adhesiveness. This fascinating SERS substrate, dependent on the flexible and adhesive Ag NW-tape, is promising for application in SERS analysis of trace residues on various practical surfaces.